Sustainable digital communication using perceived enjoyment with a technology acceptance model within higher education, in Jordan - AlDreabi, Hanadi; Halalsheh, Niveen; Alrawashdeh, Maissa N.; Alnajdawi, Ann Mousa; Alsawalqa, Rula Odeh; Al-Shboul, Muhannad (Frontiers in Education, 2023)
The technology acceptance model (TAM) has garnered considerable attention within higher education in Jordan, particularly during the COVID-19 pandemic. However, we still need to understand how to progress the TAM to enhance educational sustainability. "Perceived enjoyment" (PE) is a significant predictor of perceived ease of use, intention to use technology, use e-learning systems for educational sustainability, and attitudes toward using the TAM. This study aims to reveal the role of sustainable digital communication using PE with the TAM within higher education in Jordan. An online survey was conducted using a random sample of students at the University of Jordan, which reached 576 participants. The results of a subsequent path analysis of the survey data revealed that PE, perceived usefulness, perceived ease of use, and attitudes toward using digital communication strategies were dominant in affecting student intention to use sustainable digital communication. We found that the students would like to use digital communication strategies due to their ease of use and because they can enhance self-education. However, students need to enhance their usage skills, and to better understand digital communication strategies. Moreover, we found that the TAM, PE, perceived ease of use (PEU), and perceived usefulness (PU) immediately and favorably affect attitudes toward usage (ATU) and behavioral intention (BI). PEU negatively affected the intention of students to use technology through ATU, while PE had a significant impact on the PU, PEU, ATU, and BI of using digital communication strategies. Information and communication technologies (ICT) developers in the Jordanian Higher Education environment should create systems that are user-friendly and pertinent to the sustainability of student education, to raise their perceived ease of use. Managers should also encourage students to use ICT.